2020
DOI: 10.1002/mabi.202000183
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Coordinated Physical Gelation and Chemical Crosslinking in Gelatin Methacryloyl (GelMA) Hydrogels

Abstract: Synthetically modified proteins, such as gelatin methacryloyl (GelMA), are growing in popularity for bioprinting and biofabrication. GelMA is a photocurable macromer that can rapidly form hydrogels, while also presenting bioactive peptide sequences for cellular adhesion and proliferation. The mechanical properties of GelMA are highly tunable by modifying the degree of substitution via synthesis conditions, though the effects of source material and thermal gelation have not been comprehensively characterized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 86 publications
2
86
0
Order By: Relevance
“…Previous work has demonstrated that the viscosity of GelMA, which is thermoresponsive, can vary significantly with changes in temperature. [57][58][59] While temperature during rheological testing and printing was kept constant during experimental testing to minimize this impact, this parameter may be of particular interest when printing with cells, where it may be desired to keep ink or suspension bath temperatures at 37 0 C during printing. [57] Additionally, with the experimental setup used in this study, it was not possible to quantify the impact of needle movement in suspension baths on bath displacement or on previously deposited filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that the viscosity of GelMA, which is thermoresponsive, can vary significantly with changes in temperature. [57][58][59] While temperature during rheological testing and printing was kept constant during experimental testing to minimize this impact, this parameter may be of particular interest when printing with cells, where it may be desired to keep ink or suspension bath temperatures at 37 0 C during printing. [57] Additionally, with the experimental setup used in this study, it was not possible to quantify the impact of needle movement in suspension baths on bath displacement or on previously deposited filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine, rabbit, and chicken gelatines, hydrolyzed forms of collagens, were chosen in order to achieve close resemblance of the scaffold to extracellular matrix [43], thus maximizing the potential to produce material which may ensure sufficient viability, adhesion, and proliferation of fibroblasts [44]. Note that the source of gelatine and method of its preparation affect the ultimate mechanical and functional properties of final hydrogels [45], and consequently, the present study shall facilitate comparison of these Gel sources as a matrix of printable hydrogel.…”
Section: Polysaccharide Oxidation and Hydrogel Formationmentioning
confidence: 99%
“…Specifically, hydrogels consist of hydrophilic polymer chains embedded in a hydrated 3D environment, which allows a homogenous entrapment of multi-cell types to replicate tissue complexities [ 41 , 42 ]. In addition, molecules in hydrogel networks can diffuse through the interconnected pores, which satisfies the requirements of vasculature for the delivery of molecules from vessels to tissues [ 43 , 44 ]. Nowadays, hydrogels are widely investigated and applied for clinical therapy.…”
Section: Introductionmentioning
confidence: 99%